Forraging potentials for hybrids of maize (Zea mays L.) in the Lagoon Región. - Arreola, Jesús; Vega, Cristina; Navarro, Enrique; Burciaga, Gustavo (Agronomía Mesoamericana, 2016)
The objectives of this work were to evaluate the forage performance of several hybrids in relations with six checks. The farmer hybrids were realised by "Instituto Mexicano del Maíz", located at Saltillo, Coahuila. The agronomic traits taken into account were: grain yield and some chemical traits and their relationships with production and quality of forage in corn. Their work was divided in two parts, the first one under the field conditions in Gómez Palacio, Durango, (1992) where 25 hybrids were evaluated with a population density of 62,500 plants/ha. The analysis of variance showed no significance for production of green forage. However, one hybrid overcame the best check for more than 4 t. The second phase was carried out in the quality forage laboratory during 1992 - 1993, where each plant representing an entry was divided in three parts; later, a proximal analysis was performed and two variables were analized for green forage and ensilage. For percentage of fat, some experimentals hybrids had lower vulner than commercial hybrids in both green forage and ensilage, whereas for protein content six experimental hybrids overcame, the mean of the best checks. However, it is important to mention that the value was higher vulner of the entries for protein content were highest on ensilage than those shown for green forage whose group means were 6.91 and 6.12 respectively. In the other hand, it was posible to detect some experimental material with low vulner of fiber, mainly, in the phase of ensilage. We observed that the midde part of the plant was the richest for protein content in both ensilage and green forage. Finally, we observed the superiority of some experimental hybrids as for the parameters of contents of organic matter, portein, amount of ensilage and green forage.